2023
DOI: 10.1002/ccd.30788
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of new permanent pacemaker implantation following transcatheter aortic valve replacement

Abstract: BackgroundConduction disturbances requiring permanent pacemaker implantation (PPI) are common following transcatheter aortic valve replacement (TAVR). There were conflicting data regarding the impact of new PPI on clinical outcomes after TAVR.ObjectivesThe study sought to evaluate the impact of new PPI on clinical outcomes in patients undergoing TAVR.MethodsThis study was a retrospective analysis of prospectively collected data. Data were from 210 consecutive patients without prior PPI who underwent TAVR due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In addition, patients with a low EF had a slightly lower rate of new pacemaker implantation (11.0% vs. 12.0%, p = 0.933). This trend, while not reaching significance, provides encouraging results, considering that ventricular pacing can negatively impact outcomes in individuals with a reduced EF [21].…”
Section: Discussionmentioning
confidence: 78%
“…In addition, patients with a low EF had a slightly lower rate of new pacemaker implantation (11.0% vs. 12.0%, p = 0.933). This trend, while not reaching significance, provides encouraging results, considering that ventricular pacing can negatively impact outcomes in individuals with a reduced EF [21].…”
Section: Discussionmentioning
confidence: 78%
“…In this study, the rate of PPI was elevated at 21.5%, with a higher prevalence observed in patients receiving self-expandable valves (35.6%). While this rate exceeded that of contemporary cohorts [ 9 , 10 , 11 ], the range across the literature was highly variable, ranging from 3.4% to 25.9%, according to the 2021 guidelines on cardiac pacing [ 12 ]. Several factors contributed to this variability.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether new PPI after TAVR is associated with poorer prognostic outcomes or simply indicative of patients at elevated risk. While the PPI effectively protects against severe atrioventricular block and life-threatening insidious chronic arrhythmias ( 101 ), early evidence indicates a potential link between persistent high-frequency right ventricular pacing (RVP) and an increased risk of cardiovascular death and heart failure rehospitalization ( 102 ). Bruno's multicenter study with a 6-month follow-up on patients who underwent PPI after TAVR revealed that those with RVP ≥ 40% had significantly higher risks of cardiovascular death and hospitalization for heart failure than patients with RVP < 40% ( 103 ).…”
Section: The Types and Effects Of Conduction Abnormalities After Tavrmentioning
confidence: 99%